Getting immersed in teacher and student perspectives?: facilitating analytical competence using video cases in teacher education - Goeze, Annika; Zottmann, Jan M.; Vogel, Freydis; Fischer, Frank; Schrader, Josef (Springer, 2014)
The ability to analyze and understand classroom situations through the eyes of not only teachers but also students can be seen as a crucial aspect of teachers’ professional competence. Even though video case-based learning is considered to have great potential for the promotion of analytical competence of teachers (i.e., becoming immersed in student and teacher perspectives as well as applying conceptual knowledge to better understand classroom situations), only a few studies have investigated the effects of corresponding instructional support. This empirical field study examines the effects on analytical competence of two types of instructional support—hyperlinks to multiple perspectives and hyperlinks to conceptual knowledge—by using a 2 × 2 factorial design in a computer-supported video case-based learning environment inspired by cognitive flexibility theory and participatory design. The study examines collaborative learning processes to discover what specific kind of instruction may help to counteract some of the known deficits of case-based learning and teacher thinking, such as limited perspective-taking. From a participatory design point of view, training novices to become immersed in teacher and student perspectives can be considered as an alternative for direct involvement of teachers and students in the design process. The study was realized as a four-day university course for pre-service teachers (N = 100). ANCOVAs of learning processes (small-group discussions) and outcomes (written case analyses) provide evidence that both types of instructional support (i.e., hyperlinks to multiple perspectives and conceptual knowledge) are beneficial. In particular, hyperlinks to multiple perspectives affected small-group case discussions and written post-tests as they led to increased immersion (i.e., perspective-taking). Hyperlinks to conceptual knowledge furthered the application of this knowledge, especially in the written post-tests. Implications for teacher education, participatory design, and further research are discussed.